1986
DOI: 10.1002/bjs.1800730829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumour site on presentation, management and subsequent outcome in large bowel cancer

Abstract: To demonstrate any difference in outcome between patients with carcinoma at various sites within the large bowel, analysis of a large number of patients is necessary. From the Large Bowel Cancer Project, 4292 patients have been evaluated to compare mode of presentation, surgical management, pathological findings and outcome. Carcinoma at the splenic flexure was associated with the highest risk of obstruction (49 per cent); postoperative cardiopulmonary complications (36 per cent); in-hospital mortality (18 per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
77
5
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 26 publications
2
77
5
3
Order By: Relevance
“…Localization in the splenic flexure is observed in 4% of the patients, but this rarest localization is associated with obstruction in half of the cases. [2] Admission with acute obstruction in patients with colon cancers has been reported at rates up to 29% in different series. [3,4] The most frequent etiological factor in emergent colonic surgeries is malignancies, constituting approximately 60% of all mechanical obstructions.…”
Section: Resultsmentioning
confidence: 99%
“…Localization in the splenic flexure is observed in 4% of the patients, but this rarest localization is associated with obstruction in half of the cases. [2] Admission with acute obstruction in patients with colon cancers has been reported at rates up to 29% in different series. [3,4] The most frequent etiological factor in emergent colonic surgeries is malignancies, constituting approximately 60% of all mechanical obstructions.…”
Section: Resultsmentioning
confidence: 99%
“…Hallbook et al demonstrated in 30 patients that the side of the bowel cm above the cut proximal end has a better blood supply than the cut end. 8,13,17 The authors felt this supported the use of aside-to-end technique and hence colonic pouches, but did not comment on a difference in flow depending on whether the ascending left colic artery was preserved. Hall et al demonstrated that sigmoid colon tissue oxygen tension decreased following inferior mesenteric artery origin ligation in an elegant study involving 62 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer of splenic flexure is rare, comprising only 2% to 5% of all colorectal cancers (7)(8)(9)(10). Very few studies have specifically investigated the use of laparoscopic left hemicolectomy for cancer (11).…”
Section: Discussionmentioning
confidence: 99%
“…The optimal surgical treatment for left hemicolon cancer remains controversial. Some surgeons have argued that subtotal colectomy or extended right hemicolectomy improves oncological outcome (7,13). However, other studies have demonstrated that the prognosis for left hemi-colon cancer is no worse than for other colon cancers, and that left hemi-colectomy is sufficient for a satisfactory oncological outcome (8,9,14).…”
Section: Discussionmentioning
confidence: 99%